EFFECT OF THE ADDITION RECOMBINANT GIANT GROUPER GROWTH HORMONE (rElGH) ON FEEDWITH DIFFERENT GIVING TIME INTERVALS TOWARDS GROWTH PERFORMANCE OF FISH SEED SLICE (Ompok hypopthalmus)IN RECIRCULATION SYSTEMS - Vicky Meilia Pangestuti; Mulyadi Mulyadi; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The aim of the study was to determine the best time interval for giving recombinant Epinephelus lanceolatus GrowthHormone (rElGH) in feed to increase growth of fish seed slice (Ompok hypopthalmus)in recirculation systems. Culture vessel in the form of aquarium of 60 x 40 x 40 centimeters of 15 aquarium with stocking density of 15 fish/m3. This research was using experimental method by completely random design (RAL) one factor with five treatments and three replications, the treatments were by giving rElGH 12 mg/kg pellet with different giving time intervals. The treatments were : P1= once for a days, P2= once for three days, P3= once for five days, P4= once for seven days and P5= once for nine days. The results showed that the addition of rElGH in feed, showed highly significant effect (P<0.05) on the total weight, total length, specific growth rate, feed conversion ratio, and no significant effect (p>0.05) to survival rate. The best growth rates was found in treatment P1 with total weight: 10.96±0.45gram, total length: 8.43±7.50cm, specific growth rate: 4.51±0.06% per day, feed conversion ratio: 1.04±0.20 and survival rate: 95.6±7.50%. Keywords: Fish Slice, recombinant Epinephelus lanceolatus Growth Hormone, Growth